Dazss donut and coffee / Mas Alia Mohd Salleh - Mohd Salleh, Mas Alia (2022)
Dazs Donut and Coffee is one of the leading donut chains in Malaysia that has over 30 varieties of donut, coffee, tea and more than 20 types of cold beverages. Dazs donuts were established in 2015. At dazs donuts our passion is to provide customers with the very best doughnuts through sourcing locally with the freshnest ingredients available. Dazs donuts also popular among all ages especially kids and teenagers.